Aerodynamic Performance of a Classical Aircraft Winglet: A Parametric CFD Study - Tummala, Hari Hara Vara Prasad Rao, author; Turner, Jacob, advisor; Ciarcià, Marco, advisor; Simske, Steve, committee member; Dumitrache, Ciprian, committee member (Colorado State University. Libraries, 2026)
This thesis presents a parametric computational fluid dynamics investigation of classical aircraft winglet performance on the NASA Common Research Model (CRM) half-wing under transonic cruise conditions. Three geometric variables, winglet length, cant angle, and sweep angle, were examined using a structured three-parameter design space consisting of 216 CFD simulations. An improved trim-compensation methodology was developed to reduce artificial performance gains caused by changes in projected span and to ensure more consistent lift conditions across all configurations. The CFD results were used to construct a Chebyshev-based surrogate model for continuous evaluation of aerodynamic performance within the design space. The results show that winglet performance is governed by the coupled interaction of all three parameters rather than by any single variable alone. The most favorable configurations occurred at intermediate winglet lengths, moderate-to-high cant angles, and moderate-to-high sweep angles. The best-performing case had a winglet length of 2.7977 m, cant angle of 85.4508°, and sweep angle of 46.1803°, producing an aerodynamic efficiency improvement of approximately 1.65% relative to the baseline CRM wing. Overall, this work provides a consistent CFD-based framework for evaluating classical winglet performance using geometric trimming and surrogate modeling.
Keywords: Chebyshev Surrogate Model; Induced Drag; Winglets; Computational Fluid Dynamics; Aerodynamic Efficiency; NASA Common Research Model